ESTUDIO ANÁTOMO-HISTOPATOLÓGICO INTESTINAL EN TRATAMIENTO CON METRONIDAZOL EN ENTERITIS AGUDA INDUCIDA POR INDOMETACINA EN RATAS ALBINAS - Moscol A., Beatriz (2005)
The anatomo histopathological characteristics of the intestine in rats with acute enteritis induced by injection of one dose of indomethacine and treated with metronizadole were evaluated. Male albino Holtzman rats (n=50) were used. They were 4 months old on average and 250-275 g of body weight. Animals were equally distributed in five groups: Control (Group 1), subcutaneously injected with indomethacine (15 mg/kg) (Group 2), and injected with indomethacine plus 1, 2 or 3 doses of metronizadole (50 mg/kg) (groups 3, 4 and 5, respectively). The first dose of metronizadole was orally administered 50 minutes before the indomethacine and subsequent doses were every 5 hours. The observation of lesions was done 48 hours later. Lesions were located in the mesenteric side of the medium and distal jejune. Macroscopic lesions were characterized by thickness and dilatation of the intestinal wall, loss of the mucosa, hyperemia, and the absence of lineal ulcers longer than 10 cm. No statistical differences were found between groups treated with metronizadole (p>0.05); however, differences between these groups with the indomethacine group (p=0.021) were found. Microscopic lesions were characterized by erosion of the mucosa, presence of fibrin and mienteric plexus degeneration. No differences between the metronizadole treated groups (p>0.05) were found.